Activity‐Driven Needs Analysis and Modeling in healthcare information systems development - Luukkonen, Irmeli (Finnish Journal of eHealth and eWelfare, 2013)
Healthcare is networked, multiprofessional and cooperative work where information systems are used as means to manipulate, store and share critical and sensitive information within the work tasks of the different professionals. The changes in information systems cause changes in the work practices as well. It is important to understand the work activities where the information system will be embedded. However, the traditional information systems development (ISD) approaches are technically oriented instead of work oriented. Especially the starting point of any development project is often fuzzy and without methodologies and guidance. The research objective is to provide theoretically based, practically adaptive methods for the early phases of work oriented ISD in user organizations. Activity‐Driven Needs Analysis and Modeling was studied and developed as an integral part of larger research of Activity‐Driven (AD) ISD approach. The previous research results utilizing Activity Theory and Developmental Work Research in ISD were taken as materials to be tested and developed further in iterative research cycles. Participatory action research, case study, and constructive analysis were the main forms of the research. The empirical studies were carried on in healthcare organizations in Finland, China and Mozambique. Empirical data were gathered from the participating organizations e.g. by group and individual interviews, workshops and brainstorming sessions. Multiprofessional and multidisciplinary research groups, including “lay” healthcare professionals, have been involved to the research. The research produced knowledge about the nature of ISD in the participating organizations and methodological knowledge for supporting the starting point situations. Activity‐Driven Needs Analysis and Modeling was developed and tested; and related to mainstream methodologies, e.g. process modeling. The results of this research mainly focused on improving the applicability of the approach and the means for analysis and modeling. Specifically, the results show that the ADNA and AD Modeling fit for the starting point analysis in healthcare organizations: capturing the essence of the work activities and the information needs of the different actors within work activities, including the need for information sharing between the individuals and work activities.